The Effect of Work Environment and Compensation on Employee Work Satisfaction at Medical Appliance Company - Aprilia Riahta Millenia Sinuraya; Sanny Ekawati (International Journal of Application on Economics and Business, 2023)
The purpose of this study was to examine the effect of work environment and compensation towards employees work satisfaction at Medical Appliance Company. This study was causal research using quantitative method. The sampling method used purposive sampling technique based on certain criteria. This study had a sample size of 57 respondents. The data analysis used outer and inner model test in SmartPLS software version 3.3. The findings of this study showed that the work environment and compensation had a positive and significant effect on employee work satisfaction at Medical Appliance Company. This study can be used as a reference for Human Resource Department to make policy and decision that have an impact on increasing employee job satisfaction.